Expert Opinion on the Management of Lennox–Gastaut Syndrome: Treatment Algorithms and Practical Considerations - Cross, J. Helen; Auvin, Stéphane; Falip, Mercè; Striano, Pasquale; Arzimanoglou, Alexis (Frontiers in Neurology, 2017)
Lennox–Gastaut syndrome (LGS) is a severe epileptic and developmental encephalopathy that is associated with a high rate of morbidity and mortality. It is characterized by multiple seizure types, abnormal electroencephalographic features, and intellectual disability. Although intellectual disability and associated behavioral problems are characteristic of LGS, they are not necessarily present at its outset and are therefore not part of its diagnostic criteria. LGS is typically treated with a variety of pharmacological and non-pharmacological therapies, often in combination. Management and treatment decisions can be challenging, due to the multiple seizure types and comorbidities associated with the condition. A panel of five epileptologists met to discuss consensus recommendations for LGS management, based on the latest available evidence from literature review and clinical experience. Treatment algorithms were formulated. Current evidence favors the continued use of sodium valproate (VPA) as the first-line treatment for patients with newly diagnosed de novo LGS. If VPA is ineffective alone, evidence supports lamotrigine, or subsequently rufinamide, as adjunctive therapy. If seizure control remains inadequate, the choice of next adjunctive antiepileptic drug (AED) should be discussed with the patient/parent/caregiver/clinical team, as current evidence is limited. Non-pharmacological therapies, including resective surgery, the ketogenic diet, vagus nerve stimulation, and callosotomy, should be considered for use alongside AED therapy from the outset of treatment. For patients with LGS that has evolved from another type of epilepsy who are already being treated with an AED other than VPA, VPA therapy should be considered if not trialed previously. Thereafter, the approach for a de novo patient should be followed. Where possible, no more than two AEDs should be used concomitantly. Patients with established LGS should undergo review by a neurologist specialized in epilepsy on at least an annual basis, including a thorough reassessment of their diagnosis and treatment plan. Clinicians should always be vigilant to the possibility of treatable etiologies and alert to the possibility that a patient’s diagnosis may change, since the seizure types and electroencephalographic features that characterize LGS evolve over time. To date, available treatments are unlikely to lead to seizure remission in the majority of patients and therefore the primary focus of treatment should always be optimization of learning, behavioral management, and overall quality of life.